Relation of Language and Power in the First Modern Persian Poetry (Critical Discourse Analysis of “Vafâ-ye be ʔahd” (Adherence to the Pledge)) - Mohammadmehdi Zamani; Koorosh Safavi; Nematollah Iranzade (مطالعات زبانی و بلاغی)
The Study of relationship between language use in literary works and power links literary studies to social sciences and linguistics, Because of its high frequency of presentation of political and social subjects in Constitution literature, it has the potentiality to be studied with regard to the ideological language use and the relation of language and power, specially Persian modern poetry which has come to existence with political and social modernism. The first modern poetry was composed by Lâhuti in 1909 named “Vafâ-ye be ʔahd” (Adherence to the Pledge). Applying Fairclough’ three-dimentional model in CDA, this research studies the relation between language use and power in “Vafâ-ye be ʔahd”  in the era it is composed. Through explaining linguistic features, i.e. detailed linguistic analysis of the text indicates which discourses are articulated in the text and what relation this articulation has with power relations in the era of composing the text. To this end, Halliday’s SFG is applied in descriptive level and a part of interpretative level; and a part of Laclau and Mouffe’s discourse theory is applied in interpretative level too. The Study of this text shows that the adherence to constitution, feminism, and Islam discourses are articulated in this poetry and this articulation challenges arbitrary political regime and male-dominated social structures and propagates constitutional government and women empowering structures more than past.